THE ROLE OF "TURKESTANSKIE VEDOMOSTI" IN THE STUDY OF THE HISTORY OF THE SURKHANDARYA OASIS (SECOND HALF OF THE XIX - EARLY XX CENTURIES) - Mehriniso Olimnazarovna Begalieva (Scholar Express Journal, 2021)
This article is a historical analysis of the history of the Surkhandarya oasis, published in the second half of the XIX and early XX centuries in Turkestan, published by Russian orientalists, military, political, economic and social articles
Keywords: Surkhan oasis; Eastern Bukhara; periodicals; Russian orientalists